Thursday

April 24, 2014

April 24, 2014

Posted by **Anonymous** on Wednesday, November 4, 2009 at 4:57pm.

1 + sinx = sinx(1+cscx)

- trig -
**bobpursley**, Wednesday, November 4, 2009 at 4:59pmjust multiply the second term out

sinx + sinx*cosx=sinx + 1

**Related Questions**

Trig Help - Prove the following: [1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx...

trig - sinx+sinxcot^2x=cscx prove each identity

drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...

Trig - Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (x=theta BTW)

Pre-calc - prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i ...

trig - How do I prove these trig identities? secx-cosx/tanx =sinx And 1+sinx/...

trig - Prove (1+secx)/(tanx+sinx)=cscx